"It's in the family circle": Communication promoting Indigenous family resilience. Issue 1 (7th October 2021) - McKinley, Catherine E.; Lilly, Jenn
Abstract: Objective: We use the Framework of Historical Oppression, Resilience, and Transcendence (FHORT) to investigate the framework's core concept of family resilience and related protective and promotive factors that contribute to greater resilience, namely communication. Background: Scant research has examined communication in Indigenous families; yet general research suggests that family communication is a prominent aspect of family resilience. Methods: In this exploratory sequential mixed‐methods study with data from 563 Indigenous participants ( n = 436 qualitative and n = 127 quantitative survey), thematic reconstructive analysis was used to qualitatively understand participants' experiences of family communication and quantitatively examine protective factors for family resilience. Results: The following themes related to family communication as a component of family resilience emerged from qualitative analysis: "It's in the Family Circle": Discussing Problems as a Family with the subtheme: Honesty between Partners; (b) "Never Bring Adult Business into Kids' Lives": Keeping Adult Conversations Private; and (c) "Trust Us Enough to Come to Us": Open Communication between Parents and Children. Regression analysis indicated that higher community and social support, relationship quality, and life satisfaction were associated with greater family resilience. Conclusions: Positive communication practices are a strong component of resilience, healthy Indigenous families. Promotive factors at the community (social and community support), relational (relationship quality), and individual (life satisfaction) levels positively contribute to Indigenous family resilience. Implications: Clinical programs providing practical tools to foster healthy communication – both about difficult topics as well as positive topics – are promising avenues to foster resilience.